Role of the Principal on Teacher Pedagogic Competence - Sartika, Dewi (Journal of Education Method and Learning Strategy, 2023)
The purpose of this writing is to describe the role of school principals in improving teacher pedagogical competence and to explain the factors that inhibit the role of school principals in improving teacher pedagogical competence. The method of writing a literature study uses the approach of reviewing journal articles 16 National and 5 student thesis research results specifically based on ideas and theories about the role of school principals on teacher pedagogic competence and explaining the inhibiting factors in improving teacher competence. Based on the results of a literature study sourced from 10 journal articles and 5 student thesis results, it describes the role of school principals in improving teacher competence in the medium category, while factors the obstacle is the lack of training programs, the participation of training in increasing the competence capacity of teachers. Based on the results of the study, the authors conclude that the school principal has an important role in carrying out the duties and responsibilities attached to him, to improve the quality of teacher pedagogic competence through supervision guidance activities and training to increase the capacity of teachers as learners.